Microstructure and mechanical properties of solid-state recycled H11 steels after annealing - LIU Xinggang; LI Junpeng; MA Zhaojun; ZHANG Deliang (Fenmo yejin jishu)
To solve the poor toughness problem of the solid-state recycled H11 steels prepared by pressing and extrusion forging using the turning chip powders in different particle size, the influence of the isothermal spherodizing annealing process on the microstructure and mechanical properties of the steels was studied, and the microstructure, phase composition, and mechanical properties of the steels were characterized. The optimum isothermal spheroidizing annealing process is as follows: the temperature is rised from room temperature to 880 ℃ at the rate of 10°/min, holding for 3 h, and furnace cooling to 750 ℃, holding for 4 h, and then furnace cooling to 550 ℃, air cooling. In the results, the microstructure of the experimental steels is composed of the spherical pearlite and the dispersed granular carbide. The plasticity is improved, the elongation increases from 3.4% to 12.8%, but the tensile strength and hardness decrease. The particle size of the turning chip powders affects the strength and toughness of the solid-state recycled H11 steels after the high temperature extrusion forging. The smaller the particle size is, the worse the strength and toughness are, because of the serious oxidation after the high temperature extrusion forging.